Characterisation of Heat and Gas Emissions in Thermally Induced Battery Failure on Commercially Available 18650 Li-Ion Cells. (25th October 2017) - Lammer, Michael; Königseder, Alexander; Hacker, Viktor
Abstract : A method of holistic characterisation of thermally induced cell failure has been established. Single cylindrical cells are subjected to a defined heating ramp. Critical heat influx triggers gas generation from chemical degradation reactions. The onset of fast exothermic reactions then drives the total breakdown of cell components towards the thermal runaway. The large quantities (up to 6000 cm³) of vent gas are investigated quantitatively. H2, CO and CO2 as well as short-chain hydrocarbons are detected in this process. Thermal characterisation of endothermic and exothermic effects is performed, indicating up to 30 kJ of heat being released from a single 18650 cell during full-scale exothermic breakdown and cell deflagration.